Optimization of thread configuration in dental implants through regulating the mechanical stimuli in neighboring bone. (April 2023) - Niroomand, Mohammad Reza; Arabbeiki, Masoud; Rouhi, Gholamreza
Highlights: The effects of thread design parameters, i.e., thread depth, thread width, thread pitch, upper and lower thread angles on mechanical stimuli, i.e., maximum principal strain within the cortical and cancellous bone, and shear strain at the implant-bone interface, were investigated. Response surface method based on central composite design was employed to obtain 53 experiments for simulation by finite element method. Non-dominated sorting genetic algorithm was applied to obtain optimum thread parameter, which can keep mechanical stimuli within their safe ranges to maximize bone-implant construct stability. Abstract: Background and objective: The threads, as the most critical component of dental implants, transfer the imposed occlusal loads to the adjacent bone. Moreover, regulation of the mechanical stimuli in the implant adjacent bone is crucial to maximize the bone-implant construct stability. An optimal thread design can be resulted when the distribution of mechanical stimuli within the bone, and at the implant-bone interface, lie in an advised confined range. In this work, with the goal of finding the optimal thread design, which can provide the maximum level of stability, the effects of thread parameters, namely, thread depth, thread width, and thread pitch, together with upper and lower thread angles, on maximum principal strain within the cortical and cancellous bone, and shear strain at the implant-bone interface, were investigated. Methods: In this study, the response surface methodology (RSM), due to the central composite design (CCD), was employed to obtain a set of 53 experiments. Following that, they were numerically simulated using the finite element method (FEM). The polynomial regression model was then used to predict the response functions based on the magnitude of thread parameters. The effectiveness of each thread parameter was also evaluated through statistical tools. Moreover, the non-dominated sorting genetic algorithm (NSGA-II) was performed to find the optimum dimensions of the thread. Results: Through comparing the results obtained from analyzing initial and optimized configuration of threads, it was shown that the latter causes a reduction in the maximum principal strains in cancellous and cortical bones by about 25% and 30%, respectively, which is in favor of making a higher quality bone, and thus greater stability in dental implant-bone construct. Moreover, the maximum shear strains at the implant-bone interface in different planes were reduced by about 40%, in the optimized thread, compared with the initial design. Conclusions: The optimized design found in this study is a buttress thread with a fine pitch, but deep thread, which keeps the mechanical stimuli in a safe range to grant an acceptable level of stability. Graphical Abstract: Image, graphical abstract